2023
DOI: 10.1021/acs.est.3c02545
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Determination of Air/Water Partition Coefficients for 21 Per- and Polyfluoroalkyl Substances Reveals Variable Performance of Property Prediction Models

Abstract: Per- and polyfluoroalkyl substances (PFAS) are a group of chemicals of high environmental concern. However, reliable data for the air/water partition coefficients (K aw), which are required for fate, exposure, and risk analysis, are available for only a few PFAS. In this study, K aw values at 25 °C were determined for 21 neutral PFAS by using the hexadecane/air/water thermodynamic cycle. Hexadecane/water partition coefficients (K Hxd/w) were measured with batch partition, shared-headspace, and/or modified vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 41 publications
0
17
1
Order By: Relevance
“…In a previous article, it was shown that 1H,1H,7H-perfluoroheptyl iodide (6:1 FTI-7H) has a relatively high affinity for water compared to 6:1 FTI. The electron-withdrawing F atoms were thought to make the H atom at the terminal methyl group of 6:1 FTI-7H significantly H-bond donating . In fact, the A of 6:1 FTI-7H is positive (0.24) and higher than that of 6:1 FTI (0.13).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In a previous article, it was shown that 1H,1H,7H-perfluoroheptyl iodide (6:1 FTI-7H) has a relatively high affinity for water compared to 6:1 FTI. The electron-withdrawing F atoms were thought to make the H atom at the terminal methyl group of 6:1 FTI-7H significantly H-bond donating . In fact, the A of 6:1 FTI-7H is positive (0.24) and higher than that of 6:1 FTI (0.13).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the left side of eq was known, and MLR was performed to obtain S , A , and B on the right side. Log K false( or log nobreak0em.25em⁡ k false) c v V l L = s S + a A + b B To determine the three descriptors, a minimum of three k and K data are required for a given PFAS compound. The data used here were: k measured for 60 PFAS in this study, K Hxd/w for 21 PFAS, K ow for 12 PFAS (see the Results and Discussion section), and K oa for 3 PFAS . Note that K aw for 21 PFAS in ref was not considered here to avoid duplicate data use, as these data were derived from K Hxd/w and K Hxd/air through the thermodynamic cycle calculation.…”
Section: Materials and Methodsmentioning
confidence: 99%
See 3 more Smart Citations